Influence of Human Resource Competencies, and Information Technology on the Quality of Financial Reports of the National and Political Unity Agency of Lombok Island - Raga Solihantara; Siti Aisyah Hidayati; Endar Pituringsih (Journal of Accounting and Finance in Emerging Economies)
Purpose: This study aims to analyzev thev evffevct of human revsourcev compevtevncev, and information tevchnology on thev quality of financial revports at thev National and Political Unity Agevncy (Kevsbangpol) throughout Lombok Island